Does subtalar instability really exist? A systematic review. Issue 2 (February 2020) - Michels, Frederick; Clockaerts, Stefan; Van Der Bauwhede, Jan; Stockmans, Filip; Matricali, Giovanni
Highlights: Instability complaints can be related to subtalar ligaments injuries and increased motion of the subtalar joint. The sinus tarsi syndrome is related to lesions of the subtalar ligaments but without signs of increased subtalar motion. Brodén stress radiographs are not recommended, however, anterior drawer-supination radiographs can be considered. Clinical diagnosis should rely on several parameters including MRI. Abstract: Background: Subtalar joint instability (STI) is considered as a potential source of chronic lateral hindfoot instability. However, clinical diagnosis of STI is still challenging. This systematic review was conducted to assess the consistency of the clinical entity "subtalar instability", to investigate the reliability of available diagnostic tools and to provide a critical overview of related studies. Methods: A systematic review of the Medline, Web of Sciences and EMBASE databases was performed for studies reporting on tests to investigate subtalar instability or lesions of the subtalar ligaments. To investigate the relation with chronic STI, studies focusing on sinus tarsi syndrome (STS) or acute lesions of the subtalar ligaments were also included in the search strategy and were assessed separately. Results: This review identified 25 studies focusing on different topics: chronic STI (16), acute lesions of the subtalar ligaments (5) and STS (4). Twelve studies, assessing STI, demonstrated the existence of a subgroup with instability complaints related to abnormal increased subtalar motion (7) or abnormalities of the subtalar ligaments (6). We found insufficient evidence for measuring subtalar tilting using stress radiographs. MRI was able to assess abnormalities of the ligaments and stress-MRI detected abnormally increased motion. Conclusion: Complaints of instability can be related to subtalar ligaments injuries and an abnormally increased motion of the subtalar joint. Stress radiographs should be interpreted with caution and should not have the status of a reference test. Clinical diagnosis should rely on several parameters including MRI.